Dimensi Domain Hubungan Kekeluargaan di Selatan Johor melalui Indeks Kesejahteraan Keluarga 2017: Domain Dimension of Family Relationships in the South of Johor through the Family Well-Being Index 2017 - Siti Sarawati Johar (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
Family institutions are fundamental units of social importance in the process of human development, construction, and development, through the capacity of human capital formation. Physical development alone is meaningless if it is not accompanied by human development based on its natural nature. It is impossible to deal with internal conflicts and to challenge current family institutions because families cannot handle progressive social and economic development processes with simplicity and balance in the family. For example, when there is a disruption in family interaction, there is a loss of family relationships and non-compliance with the value system. Therefore, efforts to balance the demands of social and economic development must be consistent with strengthening relationships within family institutions, as emphasized in the Family Well-Being Index through the Family Relationships dimension. This effort is in line with the desire to create prosperity in family institutions which involves developing individuals and families in a balanced and holistic manner physically, spiritually, economically, socially and mentally. In line with that, a study aimed at testing the Family Well-Being Index was conducted on 319 respondents representing their families in the Pasir Gudang district, Johor Bahru, Malaysia, in 2017. For discussions in this study, the focus would be on the family relationships dimension in terms of Motivational Support, Togetherness, and Curiosity. Overall study findings indicate that the Family Well-Being Index for the Family Relationships dimension is at an excellent level, thus providing relevant interpretations of positive perceptions and practices among study respondents, through testing the Family Relationships domain in three main dimensions.